Measuring Corruption in Infrastructure: Evidence from Transition and Developing Countries - Kenny, Charles (2012)
This paper examines what we can say about the extent and impact of corruption in infrastructure using existing evidence. There is evidence that most perceptions measures appear to be very weak proxies for the actual extent of corruption in the infrastructure sector, largely (but inaccurately) measuring petty rather than grand corruption. Survey evidence is more reliable, but limited as a tool for differentiating countries in terms of access to infrastructure finance or appropriate policy models. The paper suggests that a focus on bribe payments as the indicator of the costs of corruption in infrastructure may be misplaced.